Dance theme in the northern desert of Chile: "Los Gitanos" - Dunin, Elsie Ivancich (Romano džaniben, 2021)
In the introduction to the Czech translation of her older paper (originally written for the International Americanist Congress in 1988) E. Dunin describes how she encountered the dance groups called "bailes", respectively its sub-group Gitanos, during the religious festival in the Atacama desert. In the paper, the author reveals a hypothesis that the style and costumes of Los Gitanos dance group composed of non-Roma were inspired by Romani migrants comming from Serbia to Chile in the 1920s/30s.
Keywords: Roma; Serbia; Chile; migration; dance; "Gypsy/Gitano" costumes